International Legal Approaches to Neurosurgery for Psychiatric Disorders - Chandler, Jennifer A.; Cabrera, Laura Y.; Doshi, Paresh; Fecteau, Shirley; Fins, Joseph J.; Guinjoan, Salvador; Hamani, Clement; Herrera-Ferrá, Karen; Honey, C. Michael; Illes, Judy; Kopell, Brian H.; Lipsman, Nir; et al. (Frontiers in Human Neuroscience, 2021)
Neurosurgery for psychiatric disorders (NPD), also sometimes referred to as psychosurgery, is rapidly evolving, with new techniques and indications being investigated actively. Many within the field have suggested that some form of guidelines or regulations are needed to help ensure that a promising field develops safely. Multiple countries have enacted specific laws regulating NPD. This article reviews NPD-specific laws drawn from North and South America, Asia and Europe, in order to identify the typical form and contents of these laws and to set the groundwork for the design of an optimal regulation for the field. Key challenges for this design that are revealed by the review are how to define the scope of the law (what should be regulated), what types of regulations are required (eligibility criteria, approval procedures, data collection and oversight mechanisms), and how to approach international harmonization given the potential migration of researchers and patients.